2019
DOI: 10.3892/ol.2019.10512
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling identifies potentially significant epigenetically‑regulated genes in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is one of the most lethal and damaging types of human cancer. The current study was conducted to identify differentially methylated genes (DMGs) between GBM and normal controls, and to improve our understanding of GBM at the epigenetic level. The DNA methylation profile of GBM was downloaded from the Gene Expression Omnibus (GEO) database using the accession number GSE50923. The MethyAnalysis package was applied to identify DMGs between GBM and controls, which were then analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…This probably also works for the other FAM72 member expressions such as FAM72A, FAM72B, and FAM72C (due to high homology (99%) in amino acid sequences) [ 25 ]. As for GBM, Kan et al could not identify epigenetically affected FAM72, though our data showed a change in the methylation status ( Figure 8 ) [ 12 , 135 ].…”
Section: Methylation Of Fam72 In Cancerous Tissuescontrasting
confidence: 57%
See 1 more Smart Citation
“…This probably also works for the other FAM72 member expressions such as FAM72A, FAM72B, and FAM72C (due to high homology (99%) in amino acid sequences) [ 25 ]. As for GBM, Kan et al could not identify epigenetically affected FAM72, though our data showed a change in the methylation status ( Figure 8 ) [ 12 , 135 ].…”
Section: Methylation Of Fam72 In Cancerous Tissuescontrasting
confidence: 57%
“…However, in non-neuronal cells, SRGAP2 expression is needed for rearranging the cytoskeleton required for cell-specific locomotion and motility and, if genomic rearranging occurs within the genomic SRGAP2 body, its tumor suppressor function is abolished, and metastasis is induced [ 26 , 132 , 133 , 134 ]. Overall, however, it appears that in cancer tissues including GBM [ 135 ], the methylation status does not have a major impact on the |-SRGAP2–FAM72-| master gene.…”
Section: Methylation Of Fam72 In Cancerous Tissuesmentioning
confidence: 99%
“…[68] DNA hypo-and hypermethylation of critical genes is also associated with malignant transformation of brain tumors. [69,70] Accumulating evidence suggests that PMT regulation by epigenetic controlled DNA methylation is associated with glioma progression. [71] Zinc finger and BTB domain containing 18 (ZBTB18) gene is a transcriptional tumor suppressor associated with brain development and neuronal differentiation.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…GBM is the most common malignant brain tumor in adults ( 34 ). Although TNF and methylation sites are proved to be associated with the progression of disease ( 35 ), the detailed mechanisms are still unclear. In this study, the bioinformatics analysis showed that there were 41 DEGs between two groups.…”
Section: Discussionmentioning
confidence: 99%